Correlation of anti-oxidant and pro-oxidant enzymes with insulin resistance in diabetic nephropathy - Alamri , Turky; Khouja, Hamed; Alrayes, Nuha; Makki, Nehad; Alhozali, Amani; Abdulnoor, Reham; Sultan, Samar (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the changes in the expression of anti-oxidant and pro-oxidant enzymes in patients with type 2 diabetes and diabetic nephropathy, and to examine their correlation with insulin resistance. Method: The case-control study was conducted from March to November 2021 at the King Abdulaziz University Hospital, Jeddah, Saudi Arabia, and comprised adult patients of either gender with diabetic nephropathy in DN group, patients with type 2 diabetes but without diabetic nephropathy in T2D group, and non-diabetic individuals in the control group. Serum insulin levels were measured using a modular analyser, while nicotinamide adenine dinucleotide phosphate oxidase, glutathione S-transferase and superoxide dismutase 3 levels were measured using enzyme-linked immunosorbent assay. Data was analysed using SPSS 29.0.1. Results: Of the 74 subjects, 45(60.8%) were females and 29(39.2%) were males. The overall mean age was 53±14 years. There were 20(27%) patients in DN group with mean age 60±11 years, 29(39.2%) patients in T2D group with mean age 56±12 years, and 25(33.8%) in the control group with mean age 43±11 years. Nicotinamide adenine dinucleotide phosphate oxidase levels were significantly lower in T2D and DN groups than in the control group (p<0.05). Glutathione S-transferase levels were significantly lower in the DN group than in the control group (p<0.05). T2D and DN groups had significantly lower superoxide dismutase 3 levels than the control group (p<0.05). Glutathione S-transferase levels correlated positively with glycated haemoglobin levels in the DN group, and negatively with fasting blood glucose levels in the T2D group (p<0.05). Superoxide dismutase 3 levels were negatively correlated with insulin and homeostatic model assessment of insulin in T2D group (p<0.05). Conclusion: Type 2 diabetes and diabetic nephropathy induced changes in the levels of superoxide dismutase 3, glutathione S-transferase and nicotinamide adenine dinucleotide phosphate oxidase. Low levels of superoxide dismutase 3 in type 2 diabetes correlated with insulin resistance, suggesting the need for anti-oxidant replacement therapy as part of diabetes control measures to prevent diabetic nephropathy. Key Words: Type 2 diabetes mellitus, Diabetic nephropathy, Insulin resistance, Oxidative stress, Anti-oxidant.